Buktikan itu? : P (AuuBuuC) = P (A) + P (B) + P (C) -P (AnnB) -P (BnnC) -P (AnnC) + P (AnnBnnC)

Buktikan itu? : P (AuuBuuC) = P (A) + P (B) + P (C) -P (AnnB) -P (BnnC) -P (AnnC) + P (AnnBnnC)
Anonim

Menjawab:

Silakan merujuk Penjelasan.

Penjelasan:

# "Prasyarat:" P (AuuB) = P (A) + P (B) -P (AnnB) …. (bintang) #.

#P (AuuBuuC) = P (AuuD), "di mana," D = BuuC #, # = P (A) + P (D) -P (AnnD) ………. karena, (bintang) #, # = P (A) + warna (merah) (P (BuuC)) - warna (biru) (P Ann (BuuC))) #, # = P (A) + warna (merah) (P (B) + P (C) -P (BnnC)) - warna (biru) (P (AnnB) uu (AnnC)), #

# = P (A) + P (B) + P (C) -P (BnnC) -warna (biru) {P (AnnB) + P (AnnC) -P ((AnnB) nn (AnnC) #, # = P (A) + P (B) + P (C) -P (AnnB) -P (BnnC) -P (AnnC) + P (AnnBnnC), #

seperti yang diinginkan!